2017
DOI: 10.1073/pnas.1616426114
|View full text |Cite
|
Sign up to set email alerts
|

Role of atmospheric oxidation in recent methane growth

Abstract: The growth in global methane (CH 4 ) concentration, which had been ongoing since the industrial revolution, stalled around the year 2000 before resuming globally in 2007. We evaluate the role of the hydroxyl radical (OH), the major CH 4 sink, in the recent CH 4 growth. We also examine the influence of systematic uncertainties in OH concentrations on CH 4 emissions inferred from atmospheric observations. We use observations of 1,1,1-trichloroethane (CH 3 CCl 3 ), which is lost primarily through reaction with OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
349
9
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 293 publications
(419 citation statements)
references
References 63 publications
22
349
9
2
Order By: Relevance
“…For the gases in this paper, potential variations in OH concentration (e.g. Rigby et al, 2017) were not found to lead to a large change in the derived emissions (see Sect. S4).…”
Section: Global Atmospheric Modelmentioning
confidence: 84%
“…For the gases in this paper, potential variations in OH concentration (e.g. Rigby et al, 2017) were not found to lead to a large change in the derived emissions (see Sect. S4).…”
Section: Global Atmospheric Modelmentioning
confidence: 84%
“…Dictated by global mass balance, the average isotopic composition of CH 4 in the atmosphere (δ 13 C-CH 4 or δD-CH 4 ) equals the flux-weighted isotopic composition of the sources, corrected for the total kinetic isotope effects of removal processes (e.g. Stevens and Rust, 1982;Cicerone and Oremland, 1988;Quay et al, 1991Quay et al, , 1999Miller et al, 2002;Turner et al, 2017;Rigby et al, 2017). It has been pointed out that assignment of representative isotopic signatures of various CH 4 sources remains uncertain due to their large spatial and temporal variability across the globe (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating δ 13 C-CH 4 and δD-CH 4 data sets in chemistry transport models is useful for quantitatively separating different CH 4 source categories and attempts have been made to reduce uncertainties in the global CH 4 budget (e.g. Hein et al, 1997;Mikaloff Fletcher et al, 2004a, b;Monteil et al, 2011;Kirschke et al, 2013;Ghosh et al, 2015;Rice et al, 2016;Schaefer et al, 2016;Schwietzke et al, 2016;Röckmann et al, 2016;Turner et al, 2017;Rigby et al, 2017). However, although an increasing number of δ 13 C-CH 4 and δD-CH 4 data have been reported over the last decades, significant measurement offsets among laboratories have been found for both δ 13 C-CH 4 (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Past work has separately used measurements of methane, its isotopes, and related gases to interpret the methane history. Two new publications (24,25) combine these complementary data into a consistent Bayesian modeling framework and use advanced statistical methods to match all observations simultaneously subject to the prior constraints. Notably, they advance our understanding of what could have caused the variability.…”
mentioning
confidence: 99%
“…So we might conclude that an important process, some chemistry-climate feedback, is missing from the 3D models. The Bayesian models used in these new papers reduce the available observations into hemispheric averages (24,25), which makes their complex statistical methods computationally tractable. However, the spatial distributions of methane, its isotopes, and MCF may contain additional information that can distinguish between the alternative scenarios and provide causal explanations for the inferred OH trends.…”
mentioning
confidence: 99%